중국어교육 관점에서 본 한자교육 방법 연구 - 교실수업 활용을 중심으로 - 장은영; Jang Eun Young (중국연구, 2019)
In this study, we described how to proceed with Chinese character education for Korean Chinese learners. This paper described the results of 'Chinese character education' class for second-grade students and 'Readings in Elementary Chinese' class for first-grade students who majoring in Chinese language in college, creating some new Chinese characters using the six categories of Chinese characters(Liu-shu), drawing pictures using some ancient Chinese characters, and writing Chinese characters using animation of the stroke order of Chinese characters. As a result, most students were interested in learning Chinese characters using various activities, and they responded that these activities would lower the burden and enhance interest in learning Chinese characters while also helping them improve their Chinese character skills. Using various methods of teaching Chinese characters that can not only help enhance learners' interest in learning Chinese characters, it is also can change their perception of Chinese characters. Furthermore, it could also help improve learners' Chinese character skills and Chinese language skills.